Perencanaan Penambangan Jangka Menengah (Quarterly Plan) Batubara Tahun 2018 Di Blok Jebak 2 PT. Nan Riang Desa Ampelu-Jebak Kecamatan Muara Tembesi Kabupaten Batanghari Provinsi Jambi - Miftahul Jannah Arida; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2018)
Abstrak. PT. Nan Riang as the Business Permit holder in the Mining Business Permit (WIUP) Region of Muara Tembesi Subdistrict, Batanghari Regency has carried out exploration activities in Jebak Block 2. There are 22 drilling exploration data points, with drill points <250 meters and moderate geological conditions with results drilling there are 2 coal seams. Mining planning needs to be made for a quarterly period in order to minimize the problems that will occur. The modeling and design of the pit was made using the Vulcan Software 9.02. From the geological modeling that produced the Block Model, the reserve was obtained at 1,568,347 tons of coal and 4,169,132 bcm overburden. The allocation of Fleet for the Quarter II of 2018 is 1 Fleet for coal and 3 Fleet for overburden. This Fleet allocation is valid until Quarter 1 of 2019. Reserved Pit quarterly design results in 2018, namely quarter II Year 2018 overburden stripping of 519,926.4 Bcm and 176,111.6 Ton Coal, quarter III of 2018 with overburden stripping of 525,476.5 Bcm and 185,521.8 tons of coal, quarter IV of 2018 with overburden stripping of 334,817.3 Bcm and 182,583.8 tons of coal and for the first quarter of 2019 with the amount of overburden 546,384.1 Bcm and 17,632.9 tons of coal. So that the total production of 2018 overburden and quarterly coal based on pit design is 1,811,701 Bcm and 720,525 tons with Striping ratio 1: 2.5.Keyword : Block Model, Design Pit, Overburden, Coal, Vulcan 9.02